Switch to Raltegravir From Protease Inhibitor or Nonnucleoside Reverse-Transcriptase Inhibitor Does not Reduce Visceral Fat In Human Immunodeficiency Virus-Infected Women With Central Adiposity. (26th April 2015) - Lake, Jordan E.; McComsey, Grace A.; Hulgan, Todd; Wanke, Christine A.; Mangili, Alexandra; Walmsley, Sharon L.; Currier, Judith S.
Abstract: Human immunodeficiency virus-infected women with central adiposity switched to raltegravir-based antiretroviral therapy immediately or after 24 weeks. No statistically significant changes in computed tomography-quantified visceral adipose tissue (VAT) or subcutaneous fat were observed, although 48 weeks of raltegravir was associated with a 6.4% VAT decline. Raltegravir for 24 weeks was associated with improvements in lipids.